Long Term Follow Up of Abdominal Aortic Aneurysms Treated With Endovascular Aneurysm Sealing (EVAS) and Endovascular Aneurysm Repair (EVAR): A Single Centre Retrospective Cohort - Simen Tveten Berge; Konstantin Valerievitch Naletov; Sven Ross Mathisen (EJVES Vascular Forum)
Objective: The Nellix endovascular aneurysm sealing (EVAS) system demonstrated promising short and midterm outcomes following its introduction in 2011. However, long term results have shown a high incidence of graft failure. This study aimed to compare the long term outcomes of EVAS compared with standard endovascular aneurysm repair (EVAR). Methods: This single centre, retrospective, comparative cohort analysis used prospectively registered data from an internal quality control registry at Innlandet Hospital Trust, Hamar Hospital, Norway. Two hundred and eighty-one patients underwent elective endovascular repair for aorto-iliac aneurysm disease between 2013 – 2016. Primary elective EVAR (n = 164) was compared with primary elective EVAS (n = 117). Results: Technical success was achieved in 100% of the EVAR and EVAS cases. The EVAS patients had a shorter hospital stay (3.7 vs. 4.7 days; p = 0.008), and lower post-procedural C reactive protein (CRP) levels (p < 0.001). No statistically significant differences were found in 30 day (p = 0.79), one year (p = 0.97), or long term all cause mortality rates, with a median follow up of 9.3 years (p = 0.93). During long term follow up, type II endoleaks were significantly less common in EVAS patients (2.6% vs. 32.3%; p < 0.001). However, EVAS had lower device durability, with freedom from device failure at five years of 54% compared with 98% for EVAR (p < 0.001). Open surgical conversion was required in 31% of EVAS patients and 2.4% of EVAR patients (p < 0.001). Aneurysm sac growth ≥5 mm was recorded in 47% of EVAS cases compared with 17.1% of EVAR cases (p < 0.001). Conclusion: While long term all cause mortality was comparable between EVAS and EVAR, EVAS was associated with statistically significantly higher rates of graft failure, aneurysm sac growth, aneurysm related death, and open surgical conversion. Close monitoring of new prosthetic devices in registries is essential to identify early signs of device failure.